Analisis Pemberdayaan Ekonomi Masyarakat Pesisir di Desa Perlis Kecamatan Brandan Barat Kabupaten Langkat - Insani, Fadhillah; Harahap, Isnaini; Syahriza , Rahmi (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2024)
Empowerment is a process of being empowered, having the strength, ability and energy to master something. As a process, empowerment is the first step for people who are powerless to become empowered where people can have strength, ability and master something that can empower their lives, both personally, in their families and in society. Empowerment of coastal communities is expected to be more empowering and improve welfare. In order to improve the community's economy and improve the Human Resources (HR) of fishing communities, of course empowerment programs must exist and be implemented to reach the fishing communities. This research aims to analyze the economic empowerment of coastal communities in Perlis Village, West Brandan District, Langkat Regency with an Enabling, Empowering and Protecting approach. The research method used is qualitative. The results of this research are that Perlis Village, with the majority working as fishermen, has potential, namely processed products from the sea in the form of sea salt, shrimp paste (belacan), and salted fish. The proceeds from sales of these products can help society improve welfare. Furthermore, fishermen who used to work in the sea looking for fish now concentrate on cultivating mud crabs and overseeing ecotourism, although there is still mangrove tourism in the area. These potentials still need to continue to be developed with the empowerment program implemented by the Perlis Village government. Regional government has four roles in community empowerment. First, the role of government regulators is to set rules to balance development implementation. Second, the government functions as a dynamist by encouraging the participation of various parties when the development process stops (encouraging and maintaining the dynamics of regional development). Third, the government functions as a facilitator by creating conducive conditions for the implementation of development (bridging the interests of various parties in optimizing regional development). Fourth, the government functions as a catalyst by encouraging the participation of various parties when the development process is stagnant.